222k views
5 votes
The equation $a^7xy-a^6y-a^5x=a^4(b^4-1)$ is equivalent to the equation $(a^mx-a^n)(a^py-a^2)=a^4b^4$ for some integers $m$, $n$, and $p$. Find $mnp$.

User Danriti
by
4.7k points

1 Answer

1 vote
Let simplify the equations
a^7xy-a^6y-a^5x=a^4(b^4-1) and
(a^mx-a^n)(a^py-a^2)=a^4b^4:

1)
a^7xy-a^6y-a^5x+a^4=a^4b^4

and

2)
a^(m+p)xy-a^(n+p)y-a^(m+2)x+a^(n+2)=a^4b^4.

Equate the coefficients:


xy: m+p=7 \\ y: n+p=6 \\ x: m+2=5 \\ 1: n+2=4.

Then
n=2 \\ p=4 \\ m=3 and mnp=24.

User Your Friend
by
5.4k points